Pengaruh Kualitas Layanan dan Perilaku Peran Ekstra terhadap Kepuasan Pasien Rumah Sakit Bersalin di Propinsi Sulawesi Utara - Silvya Mandey (Jurnal Aplikasi Manajemen, 2012)
This study tested the influence of service quality and extra-role behavior partially and simultaneously to patients. Cluster sampling technique used to obtain samples of 70 patients who have a toddler and had a normal childbearing at their own expense.Keywords: Service Quality, Extra-role behavior, patient satisfaction